SERTIFIKASI GURU DAN IMPLIKASINYA TERHADAP KUALITAS PEMBELAJARAN - Fela Hadziqoh; Arni Muliati; Rosida; Rera Oktariya; Eni Heldayani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the implications of teacher certification on the quality of learning by examining pedagogical aspects and TPACK-based technology integration. The research was conducted at SDN 131 Palembang for 20 days using a qualitative approach with participant observation, semi-structured interviews and documentation methods. Observations were conducted to examine classroom interactions and the use of instructional technology. The findings indicate that certified teachers generally demonstrate good pedagogical competence and are able to create interactive learning environments. However, the implementation of TPACK varies, and not all teachers optimally integrate technology into their teaching practices. In addition to certification, factors such as teacher motivation, school environment, and facility support also influence learning quality. Therefore, teacher certification alone does not fully guarantee improved learning quality without continuous professional support.